Gdh 2004 - Proceedings Of The Third International Symposium On The Gerasimovdrellhearn Sum Rule And Its Extensions. - Kuhn, Sebastian (World Scientific, 2005)
This volume presents an overview of the many new and exciting results, both theoretical and experimental, in the area of spin structure functions and sum rules at low to moderate photon virtuality Q2. It includes contributions from many leading scientists in the field worldwide. The volume covers the following topics:. recent results on the GerasimovDrellHearn (GDH) sum rule with real photons and its extensions to virtual photons. inclusive spin structure functions at low to moderate Q2 and their moments. exclusive measurements of nucleon spin structure in the resonance region. spin.